Legacy and current pesticide residues in Syr Darya, Kazakhstan: Contamination status, seasonal variation and preliminary ecological risk assessment. (1st October 2020) - Snow, D.D.; Chakraborty, P.; Uralbekov, B.; Satybaldiev, B.; Sallach, J.B.; Thornton Hampton, L.M.; Jeffries, M.; Kolok, A.S.; Bartelt-Hunt, S.B.
Abstract: The Syr Darya is one of two major rivers in Central Asia supplying critical fresh water to the Aral Sea. In spite of the river's importance and agriculturally-intensive history, few studies have provided a modern evaluation of and the occurrence of pesticide residues potential effects to aquatic life. The primary goal of this investigation was to determine seasonal variations in ambient concentrations of modern and legacy pesticides in bottom sediment and water of the Syr Darya in Kazakhstan (KZ) downstream from an agriculturally-intensive watershed in Uzbekistan. Grab samples and passive samplers were used at five remote sampling stations during June 2015 to provide a baseline for ecotoxicological evaluation. Results were compared with samples collected during and after the agricultural growing season. Polar organic chemical integrative samplers (POCIS) were used in June and calibrated for time-weighted average concentrations of current use pesticides. Among legacy chlorinated pesticides measured in grab samples from the river, lindane (γ-HCH) was detected most frequently with the highest concentrations occurring during June. For all the sampling events, residues of lindane (γ-HCH) ranged from 0.014 to 0.24 μg/L detected in water samples, are among the highest concentrations reported for rivers globally. Concentrations of γ -HCH, p, p' -DDE and dieldrin were highest in October when dieldrin concentrations approached 0.4 μg/L. Sources of legacy pesticides may be either illicit upstream use or evidence of previous atmospheric contamination of glacial meltwater. Chronic exposure to these residues may lead to ecological risk to lower order organisms in both the sediment and water column. Graphical abstract: Image 1 Highlights: Modern and banned "legacy" pesticides are present in the Syr Darya. Organochlorine contaminants occur throughout irrigation season. Ecologic risks from exposure to aquatic organisms are likely. Passive and grab sampling help monitor contaminants in remote watersheds.